PERUBAHAN KERAPATAN MANGROVE BERDASARKAN KARAKTERISTIK CITRA LANDSAT DI PESISIR KABUPATEN TANAH LAUT - Nursalam Nursalam; Muhammad Syahdan; Algui Sumas Ponaru (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Monitoring of mangrove vegetation in the long-time vulnerable is needed to determine its conversion as the first step of mangrove management. The purpose of this study mapped the spatial distribution of mangrove vegetation and discribed the change of mangrove vegetation area in the coastal area of Tanah Laut Regency for 12 years. The method was used remote sensing and method field obeservation. The mangrove density of 2003 is dominated by medium density and by 2015 is dominated by dense density. The area of mangrove density rarely increased by 375.87 ha. The area of density is decreasing the area of 1.454,16 ha. Density of density increased by 1,639.77 ha.